2022
DOI: 10.2196/38347
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Digital Skills of Catalan Health Care Professionals as a Key Step Toward a Strategic Training Plan: Digital Competence Test Validation Study

Abstract: Background Despite Catalonia being an advanced region in terms of digital health adoption, the “Forum for Professional Dialogue” identified the need to improve information and communication technology (ICT) competences as one of the present and future challenges for health care professionals (HPs). Objective We aimed to validate the digital competence test developed ad hoc for this study and to measure the digital competence level of Catalan HPs to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Slovenia, Denmark, and Italy do not currently have an established national programme/plan for improving the digital health competencies among HCPs, although the importance of digital skills was acknowledged ( Table 4 ). In Catalonia, the COMPDIG-Salut project [ 44 ], adopted in 2020 together with the Professional Dialogue Forum, is a specific programme that aims to provide a digital skills framework and specific accreditation for HCPs. University programmes usually offer basic digital skills training in all included countries, although digital health competencies are mainly acquired on the job during clinical practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slovenia, Denmark, and Italy do not currently have an established national programme/plan for improving the digital health competencies among HCPs, although the importance of digital skills was acknowledged ( Table 4 ). In Catalonia, the COMPDIG-Salut project [ 44 ], adopted in 2020 together with the Professional Dialogue Forum, is a specific programme that aims to provide a digital skills framework and specific accreditation for HCPs. University programmes usually offer basic digital skills training in all included countries, although digital health competencies are mainly acquired on the job during clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Number 4 was focused on the need to improve the ICT skills of health professionals, and to advance both in the use of ICT to favour personalized care and the design of non-face-to-face care services. Following the Professional Dialogue Forum, the COMPDIG-Salut project [44] has been conceived with the aim of providing a digital skills framework and a specific accreditation for Catalan healthcare professionals. COMPDIG-Salut and the Professional Dialogue Forum are still active and working to fulfil their main objectives.…”
Section: Do Healthcare Providers Have the Freedom To Implement Additi...mentioning
confidence: 99%
“…The definitions used are either the results of scoping reviews or frameworks where many individual results have been merged (15/46, 33%) [4,10,23,26,28,33,37,42,44,46,48,51,52,59,61]. Alternatively, they are based on other, explicitly named works, such as DigComp 2.2 [7] (4/46, 9%) [22,29,54,56]; the European framework for the digital competence of educators [63] (1/46, 2%) [27]; the technology acceptance model [64] and the unified theory of acceptance and use of technology [65] (1/46, 2%) [11]; the accreditation of competence in information and communication technologies by the government of Catalonia [66] (1/46, 2%) [53]; the Educause Center for Analysis and Research [67] (1/46, 2%) [60]; the General Confidence with Computer Use Scale [68] (1/46, 2%) [32]; the eHealth literacy questionnaire [69] (1/46, 2%) [40]; the eHealth literacy assessment toolkit [70] (1/46, 2%) [34]; the Self-Assessment of Nursing Informatics Competencies Scale [71] (1/46, 2%) [24]; a scale assessing the informatics competencies for nurses [72] (1/46, 2%) [39]; a scale assessing digital literacy with regard to information and communication technology [73] (1/46, 2%)…”
Section: Most Of the Papers Provided Definitions In Which Digital Com...mentioning
confidence: 99%
“…There are few definitions of digital skills, and skills can be seen as an attribute to digital competence. 8 , 9 The overlap of the two concept definitions makes it challenging to describe digital skills. Skills in general means the ability to apply and use knowledge to complete tasks and solve problems.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Challenges have also been related to physical examination and assessment of patients via digital tools 1 as well as ethical practice, such as respecting patients’ privacy and confidentiality during the digital appointment. 20 Recent studies assessing HCPs’ digital skills indicated that majority of participants ( n = 803) demonstrated basic level of digital competence, 8 whereas in low-income countries ( n = 167) the level was relatively low. 21 There is a research gap in assessing HCPs’ current digital skills in cancer care, and no previous literature review has been reported on the subject so far.…”
Section: Introductionmentioning
confidence: 99%